INTERVENTION TO IMPROVE ANTIRETROVIRAL ADHERENCE AND QUALITY OF LIFE ON HIV/AIDS : A SYSTEMATIC REVIEW - Amalia Fardiana; Nursalam Nursalam; Faizah Maulidiyah (Universitas Airlangga, 2022)
Introduction: : HIV/AIDS first appeared in Indonesia in 1987 which until now continues to spread in 386 regencies / cities in Indonesia. The high rate of HIV/AIDS in Indonesia requires patients to improve the compliance and continuity of treatment with the help of doctors or health workers, escorts and supported by the availability of drugs. This study aims to find out the effective mobile intervention to improve the compliance of ARV and QOL treatment of patients with HIV/AIDS Method: The method used in systematic review uses protocols and rules that are suitable by using flow diagram. Feasibility of the study was assessed using picot framework with population of HIV/AIDS patients undergoing ARV therapy, the intervention used is mobile intervention which includes mobile reminder and mobile education Results: The results include journal results from the search database Science Direct, Scopus, Proquest, and PubMed using 12 journals. The intervention consists of mobile intervention such as education and counseling. These interventions have been shown to improve treatment adherence, quality of life, and/or both. Conclusion: There needs to be contributions from various parties to be able to improve the adherence of treatment and Qol, not only from patients and health workers but also families. mobile intervention is quite effective given to HIV patients in carrying out treatment adherence therapy as well as improving QOL in patients. Keywords: education; HIV/AIDS; mobile; online; telehealth